Jews in Italy under Fascist and Nazi rule, 1922 - 1945 - Zimmerman, Joshua D. 1966- (Univ. Press, 2005)
The double-bind of Italian Jews: acceptance and assimilation / Alexander Stille -- Italian Jewish identity from the Risorgimento to Fascism, 1848-1938 / Mario Toscano -- Mussolini and the Jews on the eve of the march on Rome / Giorgio Fabre -- Characteristics and objectives of the anti-Jewish racial laws in Fascist Italy, 1938-1943 / Michele Sarfatti -- The exclusion of Jews from Italian academies / Annalisa Capristo -- The damage to Italian culture: the fate of Jewish university professors in Fascist Italy and after, 1938-1946 / Roberto Finzi -- Building a racial state : Images of the Jew in the illustrated Fascist Magazine, La difesa della razza, 1938-1943 / Sandro Servi -- The impact of anti-Jewish legislation on everyday life and the response of Italian Jews, 1938-1943 / Iael Nidam-Orvieto -- The children of Villa Emma at Nonantola / Klaus Voigt -- Anti-Jewish persecution and Italian society / Fabio Levi -- The Shoah in Italy : its history and characteristics / Liliana Picciotto -- The M(c)·ollhausen telegram, the Kappler decodes, and the deportation of the Jews of Rome: the new CIA-OSS documents, 2000-2002 / Robert Katz -- The persecution of Jews in two regions of German-occupied northern Italy, 1943-1945 : Operationszone Alpenvorland and Operationszone Adriatisches K(c)·ustenland / Cinzia Villani -- The papal response to Nazi and Fascist anti-semitism : from Pius XI to Pius XII / Frank J. Coppa -- Pius XII and the rescue of Jews in Italy : evidence of a papal directive / Susan Zuccotti -- The rescued and the rescuers in private and public memories / Anna Bravo -- Return of the repressed : Italian film and Holocaust memory / Millicent Marcus -- The secret histories of Roberto Benigni's Life is beautiful / Ruth Ben-Ghiat